2015
DOI: 10.1016/j.aenj.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Spinal immobilisaton in pre-hospital and emergency care: A systematic review of the literature

Abstract: There are no published high-level studies that assess the efficacy of spinal immobilisation in pre-hospital and emergency care settings. Almost all of the current evidence is related to spinal immobilisation is extrapolated data, mostly from healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 57 publications
(138 reference statements)
0
28
0
3
Order By: Relevance
“…Since then, immobilization has become a standard procedure in emergency medicine [2]; however, a recent study found that 20% of patients suffering from a cervical SCI were not immobilized whatsoever by emergency care providers [4]. A possible explanation is the fact that, over the years, no evidence for the benefit of immobilization for patient outcomes has been obtained from rigorous studies (e.g., randomized controlled trials) [5][6][7]. Furthermore, regardless of the method, immobilization has its disadvantages, such as general patient manipulation, pain, decubitus, and prolonged pre-hospital time [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, immobilization has become a standard procedure in emergency medicine [2]; however, a recent study found that 20% of patients suffering from a cervical SCI were not immobilized whatsoever by emergency care providers [4]. A possible explanation is the fact that, over the years, no evidence for the benefit of immobilization for patient outcomes has been obtained from rigorous studies (e.g., randomized controlled trials) [5][6][7]. Furthermore, regardless of the method, immobilization has its disadvantages, such as general patient manipulation, pain, decubitus, and prolonged pre-hospital time [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy was adopted by many prehospital medical services worldwide as well as on trauma courses such as Prehospital Trauma Life Support (PHTLS®) and Advanced Trauma Life Support (ATLS®) [2, 3]. This change occurred despite a lack of high-quality study data to suggest clear benefits [46]. On the contrary, a growing body of evidence during recent years indicates that the use of the rigid cervical collar and the hard backboard might indeed have harmful effects.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Both the safety and efficacy of traditional SI have come into question in recent years and as a result some emergency medical services (EMS) agencies have deemphasized the use of LSBs and c-collars. [2][3][4][5] These changes have been implemented based on new evidence that highlights the low incidence of spinal cord injury (SCI), potential harm from the application of these devices, [6][7][8][9][10][11][12] and lack of evidence demonstrating any positive effect on mortality, spinal stability, or neurologic injury. [5,13] Several studies have highlighted specific associations between the use of SI devices and predictors of negative outcomes following trauma, including increased intracranial pressure with c-collar use after traumatic brain injury, [14] as well as increased time spent on scene by EMS personnel, decreased intubation success, and decreased respiratory capacity.…”
Section: Introductionmentioning
confidence: 99%